2011
DOI: 10.1007/s00122-011-1585-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeted discovery of quantitative trait loci for resistance to northern leaf blight and other diseases of maize

Abstract: To capture diverse alleles at a set of loci associated with disease resistance in maize, heterogeneous inbred family (HIF) analysis was applied for targeted QTL mapping and near-isogenic line (NIL) development. Tropical maize lines CML52 and DK888 were chosen as donors of alleles based on their known resistance to multiple diseases. Chromosomal regions ("bins"; n = 39) associated with multiple disease resistance (MDR) were targeted based on a consensus map of disease QTLs in maize. We generated HIFs segregatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 77 publications
4
46
0
Order By: Relevance
“…Most publications designate GLS QTL into maize core bins [3,4,7,25-27]. A maize genome bin has been defined as one of the 100 designated chromosomal segments between two core RFLP markers (http://www.maizegdb.org/cgi-bin/bin_viewer.cgi).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most publications designate GLS QTL into maize core bins [3,4,7,25-27]. A maize genome bin has been defined as one of the 100 designated chromosomal segments between two core RFLP markers (http://www.maizegdb.org/cgi-bin/bin_viewer.cgi).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies employed populations of recombinant inbred lines (RIL), such as the intermated B73 X Mo17 (IBM) population, which allowed repeated GLS disease testing in multiple environments coupled with high density molecular marker maps [25-27]. QTL for GLS resistance were located to regions down to 3 cM [25].…”
Section: Introductionmentioning
confidence: 99%
“…In a QTL study of the recombinant inbred line (RIL) population Ki14 3 B73 evaluated for three foliar fungal diseases, NLB, GLS, and SLB, a 33-Mb region spanning bins 1.05 and 1.06 was the only locus identified that conferred resistance to all three diseases (Zwonitzer et al 2010). A number of QTL studies for NLB resistance in maize have identified QTL at bin 1.06, ranging in physical size from 3 to 30 Mb (Freymark et al 1993;Welz et al 1999;Wisser et al 2006;Chung et al 2010bChung et al , 2011Van Esbroeck et al 2010;Poland et al 2011). Additionally, bin 1.06 harbors the dominant Stewart's wilt resistance gene Sw1 (Ming et al 1999).…”
mentioning
confidence: 99%
“…At the chromosomal segment level, disease and insect resistance loci colocalize in a nonrandom fashion (McMullen and Simcox 1995;Williams 2003;Wisser et al 2005) and loci have been identified that confer resistance to diverse pathogen isolates and taxa (Zwonitzer et al 2010;Chung et al 2011;Belcher et al 2012). There is evidence to suggest that gene clusters can confer resistance to more than one disease.…”
mentioning
confidence: 99%
“…In addition, these two genome regions were also found to confer resistance to multiple potyviruses, including SCMV, MDMV, ZeMV, and WSMV (Lubberstedt et al 2006). To investigate genomic regions associated with MDR in maize, Chung et al (2011) adopted heterogeneous inbred families (HIFs) and RILs to survey their response to eight diseases, discovering two MDR QTL, one QTL in bin 1.06/1.07 conferred resistance to NLB and Stewart's wilt, and another in bin 6.05 conferring resistance to NLB and ASR. Two reliable QTL conferring resistance to NLB were also found to be involved in MDR of maize, with qNLB1.02 B73 associated with resistance to Stewart's wilt and common rust, and qNLB1.06 Tx303 conferring resistance to Stewart's wilt as well (Chung et al 2010b).…”
Section: Genes Conferring Resistance To Biotic Stresses In Maizementioning
confidence: 99%